Social Exclusion of Youth in Europe: The Multifaceted Consequences of Labour Market Insecurity - Marge Unt; Michael Gebel; Sonia Bertolini; Vassiliki Deliyanni-Kouimtzi; Dirk Hofäcker (Policy Press, 2021)
Policymakers throughout Europe are enacting policies to support youth labour market integration. However, many young people continue to face unemployment, job insecurity, and the subsequent consequences. Adopting a mixed-method and multilevel perspective, this book provides a comprehensive investigation into the multifaceted consequences of social exclusion. Drawing on rich pan-European comparative and quantitative data, and interviews with young people from across Europe, this text gives a platform to the unheard voices of young people. Contributors derive crucial new policy recommendations and offer fresh insights into areas including youth well-being, health, poverty, leaving the parental home, and qualifying for social security.
Keywords: 300; European Comparison; Job Security; Social exclusion; Transition to Adulthood; Unemployment; Youth